PTU-142 How Common are Delays in Referral of Patients with Oesophageal Cancer from Primary Care?. (4th June 2013) - Cheung, D; Trudgill, N
Abstract : Introduction: The UK has the highest age-standardised incidence of oesophageal cancer (OC) in Europe with a 5 year survival rate of only 11.6%. We have investigated a large primary care cohort to determine how common delays in referral are and associated factors. Methods: All subjects with OC from the Health Improvement Network (THIN) primary care database were studied. THIN includes over 6 million patients and is regionally and demographically representative of the UK. A nested case-control study was performed with cases of 'delayed referral' defined as subjects who met NICE guidance for urgent referral (August 2004) with alarm upper gastrointestinal (UGI) symptoms (dysphagia, weight loss, abdominal mass, recurrent vomiting, UGI bleed, iron deficiency anaemia) or dyspepsia over 55 years but were not referred within 14 days. Control subjects were referred within 14 days. Logistic regression analysis assessed associations with delayed referral. Results: 4210 subjects had OC diagnosed after August 2004. 567 (377 (66.5%) male) had a referral date recorded and were analysed. Mean age 70.7 ± 11.2 years with 1.4 ± 0.8 mean consultations prior to referral. Presenting symptoms of OC: dysphagia 326 (57.5%), dyspepsia 174 (30.7%), anaemia 31 (5.5%), weight loss 23 (4.1%), recurrent vomiting 6 (1.1%), UGI bleed 6 (1.1%) and abdominal mass 1 (0.2%). 355 (62.6%) referred within 14 days with mean lag time of 1.9 ± 3.0 days. 212 (37.4%) had a potential referral delay: 60 (10.6%) 14–29 days; 103 (18.2%) 30 days-1 year; 49(8.6%) > 1 year; with mean lag time of 273.0 ± 433.1 days. Time from presentation to OC diagnosis in the controls was 63.8 ± 155.1 days compared with 3413 ± 469.7 days in the delayed referral group, with 0.8 ± 0.9 extra consultations prior to referral. There was no difference in age at presentation (70.2 ± 11.0 years (delayed referral), 70.2 ± 11.3 years (controls), P = 0.5) and no association with male gender (1.15 (95%CI 0.8–1.6), p = 0.46) or Townsend index (group 1–2 versus group 4–5, 0.95 (95%CI 0.6–1.4), p = 0.8) for referral delay. Subjects with dysphagia were less likely to experience referral delay (0.15 (95%CI 0.1–0.2), p = < 0.0001) compared with other alarm symptoms. However, delayed referral did not significantly affect oesophagectomy rate (14.6% vs 16.9%, 0.72 (95%CI 0.4–1.2), p = 0.18) or 1 year survival (43.8% vs 44.1%, 0.98 (95%CI 0.7–1.5), p = 0.95). Conclusion: A third of patients were not promptly referred to secondary care despite meeting NICE criteria leading to diagnosis delays. 80% of subjects with dysphagia were referred promptly, but only 39% of subjects with other alarm symptoms or new dyspepsia. Surprisingly, delayed referral did not affect surgical resection or 1 year survival rate. Disclosure of Interest: None Declared